If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 58 = 4h Solving 58 = 4h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-4h' to each side of the equation. 58 + -4h = 4h + -4h Combine like terms: 4h + -4h = 0 58 + -4h = 0 Add '-58' to each side of the equation. 58 + -58 + -4h = 0 + -58 Combine like terms: 58 + -58 = 0 0 + -4h = 0 + -58 -4h = 0 + -58 Combine like terms: 0 + -58 = -58 -4h = -58 Divide each side by '-4'. h = 14.5 Simplifying h = 14.5
| 9.05x=27.15 | | 6/2x3 | | 0.5(r-12)=4 | | (x)/(4)-1=7 | | 0.4(b+2)=2 | | 9(x-2)+1=9x-16 | | 19-6(-k+4)= | | .50(x-3)=2(x-3) | | 6n+3n=108 | | f(-4)+f(3)= | | 30u^5v^3x^6+24u^8v^9= | | (4-2i)(3+i)= | | r*2+2r+12=0 | | 5.6+x=8.4 | | 3(19/-23)=20(-19/-23)-7 | | 3(19/-23)=20(-19/23)-7 | | 16x-3x=3(2-x) | | (3x^7)(-5x^3)= | | 12=-7y | | Xa+xb=3c | | x^4-x^3-24x^2+37x+60=0 | | 7(-8c+9a)= | | -3(4m+7)= | | 12=-11y+4y | | (-7v-6)-(2v-4)= | | 6(2+15x)= | | 2/7-1/14 | | 32b-4+-2b-1= | | 10+5r=10-r | | (2/x)-x=(-23/5) | | (7/8)/m=(1/7) | | =(2a+3b-4c) |